2005
DOI: 10.1088/0964-1726/14/4/003
|View full text |Cite
|
Sign up to set email alerts
|

Active control of piezolaminated columns—exact solutions and experimental validation

Abstract: The present paper demonstrates the effect of axial forces on smart columns that have adhesively bonded piezoelectric skins on substrates. Exact solutions for the piezolaminated columns have been presented. The solutions have been validated through experimental studies. The objectives of the present work are (1) to show the effect of axial force on sensing and actuation mechanisms of piezoelectric materials and (2) to demonstrate the active control of column type structures using these materials. In the experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The piezoelectric PVDF and its copolymers are widely applied materials in both actuation and sensing mechanisms. They can be utilized as fibers and films mostly in linear movement requirements in various engineering applications such as active micro air vehicle wings 4 , piezolaminated columns 18 , and shape correction films in space applications 19 . Other applications may include: Proton exchange membranes 20 , filtration membranes 21 , structural health monitoring 22 , endoscopic tactile sensors 23 , and macrofluidic control 24 , Kwon and Dzenis, for instance, embedded PVDF films of tens of microns thick into the graphite/epoxy (CFRP) composite laminates to monitor the tensile failure of unidirectional CFRP laminates 25 .…”
Section: Introductionmentioning
confidence: 99%
“…The piezoelectric PVDF and its copolymers are widely applied materials in both actuation and sensing mechanisms. They can be utilized as fibers and films mostly in linear movement requirements in various engineering applications such as active micro air vehicle wings 4 , piezolaminated columns 18 , and shape correction films in space applications 19 . Other applications may include: Proton exchange membranes 20 , filtration membranes 21 , structural health monitoring 22 , endoscopic tactile sensors 23 , and macrofluidic control 24 , Kwon and Dzenis, for instance, embedded PVDF films of tens of microns thick into the graphite/epoxy (CFRP) composite laminates to monitor the tensile failure of unidirectional CFRP laminates 25 .…”
Section: Introductionmentioning
confidence: 99%
“…cantilever column with a tip mass controlled in a similar way was investigated both theoretically and experimentally by Mukherjee and Chaudhuri [3]. The experiment confirmed that a properly chosen gain multiplier, which enhances the signal from piezo sensors to actuators, can be used to control the active damping in the structure and demonstrated the efficacy of piezoelectric materials in vibration control.…”
Section: Introductionmentioning
confidence: 74%
“…Here, p is a proportionality coefficient chosen as p = 10,000 Vs/m. The maximum voltage was restricted to the breakdown voltage assumed to be V max = 1000 V. Velocity feedback has been used, for example, for dynamic instability control of piezolaminated columns by Mukherjee and Saha Chaudhuri [121][122][123].…”
Section: Control Of Nonlinear Dynamic Problemsmentioning
confidence: 99%